Analisis Perbandingan Respons Seismik Gedung Beton Bertulang 10 Lantai dengan Sistem Shear Wall dan Base Isolation High Damping Rubber Bearing (HDRB) - Hidayatullah, Rajib Rizkul; Sutriono, Bantot (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Earthquakes have the potential to cause significant damage to multi-story buildings; therefore, structural systems that can improve seismic performance are required. This study aims to compare the structural response of a 10-story office building in Surabaya using fixed base, shear wall, and base isolation systems with High Damping Rubber Bearing (HDRB). The analysis was conducted using ETABS software in accordance with SNI 1726:2019, considering parameters such as inter-story drift, base shear, structural period, and P-Delta effects. The results indicate that the shear wall system provides the highest stiffness, while the HDRB system significantly increases the structural period and reduces inter-story drift in the upper structure. Although it results in larger deformation at the base, the HDRB system still meets the performance criteria and is recommended for buildings in seismic-prone areas.